Chimeric Antigen Receptor Signaling Domains Differentially Regulate Proliferation and Native T Cell Receptor Function in Virus-Specific T Cells - Omer, Bilal; Castillo, Paul A.; Tashiro, Haruko; Shum, Thomas; Huynh, Mai T. A.; Cardenas, Mara; Tanaka, Miyuki; Lewis, Andrew; Sauer, Tim; Parihar, Robin; Lapteva, Natalia; Schmueck-Henneresse, Michael; et al. (Frontiers in Medicine, 2018)
The efficacy of T cells expressing chimeric antigen receptors (CARs) for solid tumors has been limited by insufficient CAR T cell expansion and persistence. The use of virus-specific T cells (VSTs) as carriers for CARs may overcome this limitation since CAR-VSTs can be boosted by viral vaccines or oncolytic viruses. However, there is limited understanding of the optimal combination of endodomains and their influence on the native T cell receptor (TCR) in VSTs. We therefore compared the function of GD2.CARs expressing the TCR zeta chain (ζ) alone or combined with endodomains from CD28 and 4-1BB in varicella zoster virus-specific (VZV) T cells. VZVSTs expressing GD2-CARs recognized VZV-derived peptides and killed GD2-expressing tumor cells. However, after repeated stimulation through their native TCR, the expansion of GD2-CAR.CD28ζ-VZVSTs was 3.3-fold greater (p<0.001) than non-transduced VZVSTs, whereas GD2-CARζ- and GD2-CAR.41BBζ inhibited VZVST expansion (p<0.01). Compared to control VZVSTs, GD2-CAR.ζ VZVSTs showed a greater frequency of apoptotic (p<0.01) T cells, whereas prolonged downregulation of the native αβ TCR was observed in GD2-CAR.41BBζ VZVSTs (p<0.001). We confirmed that CD28ζ can best maintain TCR function by expressing GD2.CARs in Epstein-Barr virus-specific T cells and CD19-CARs in VZVSTs. In response to CAR stimulation VSTs with CD28ζ endodomains also showed the greatest expansion (six fold greater than GD2-CAR.41BBζ VZVSTs (p<0.001)) while in ATCs GD2-CAR.41BBζ modification resulted in the highest proliferation. These findings demonstrate that CAR signaling domains can enhance or diminish the function of the native TCR and indicate that CD28ζ might be the optimal CAR in VSTs.